PENGARUH CAPITAL ADEQUACY RATIO, NON PERFORMING LOAN, DAN LOAN TO DEPOSIT RATIO PADA PROFITABILITAS - Dania, Ayu Prima; Sujana, I Ketut (E-Jurnal Akuntansi, 2015)
Profitability indicates how efficiently an LPD has been operating. There are several things that affect the development of profitability LPD include capital adequacy, problem loans and funds from third parties. There are several ratios that are used to measure three things can affect the profitability of an LPD. The ratio of these, capital adequacy ratio, non-performing loans and loan-to-deposit ratio. The purpose of this study was to determine the effect of capital adequacy ratio, non-performing loans and loan-to-deposit ratio on the profitability of LPD in Badung. This research was done on the LPD in Badung. The samples used in this study were 122 LPD. The data used is secondary data and using purposive sampling method in determining the sample. Data analysis techniques used multiple regression analysis. Based on the results of multiple linear regression showed capital adequacy ratio positive effect on the profitability of LPD, non-performing loans have negative effect on the profitability of LPD, loan to deposit ratio has positive effect on the profitability of LPD.
Keywords: capital adequacy ratio, non performing loan, loan to deposit ratio, profitability